Examine the Mechanical Properties of Recycled Coarse Aggregate with MK GGBS. Issue 1 (April 2021) - Sharma, Prashant; Verma, Mohit; Sharma, Neha
Abstract: This paper present the laboratory investigation on replacing of Natural Coarse Aggregate (NCA) with Recycled Coarse Aggregate (RCA) in concrete while Cement is replaced by Metakaolin (MK) and GGBS (Ground Granulated Blast-furnace Slag), as varying content of GGBS as 10%, 15%, 20%, and 25% with amount of MK was fixed at 10% by weight. In concrete mix specimens, NCA was replaced with RCA by 10%, 20%, 30%, 40% and 50% by weight. To understand the fresh properties of concrete, slump test was performed and found satisfactory result. To analyse hardened properties of MK GGBS based recycled aggregate concrete mix, compressive strength at curing ages of 7, 28 and 56 days while flexural strength were performed at 28 curing days. Mix id 43 explored the optimum compressive strength. From the experiments study, it can be concluded that the 30% replacement of NCA carried good result with 10% MK and 20% GGBS.